Effects of Training and Competition Load on Neuromuscular Recovery, Testosterone, Cortisol, and Match Performance During a Season of Professional Football - Rowell, Amber E.; Aughey, Robert J.; Hopkins, William G.; Esmaeili, Alizera; Lazarus, Brendan H.; Cormack, Stuart J. (Frontiers in Physiology, 2018)
Introduction: Training load and other measures potentially related to match performance are routinely monitored in team-sport athletes. The aim of this research was to examine the effect of training load on such measures and on match performance during a season of professional football. Materials and Methods: Training load was measured daily as session duration times perceived exertion in 23 A-league football players. Measures of exponentially weighted cumulative training load were calculated using decay factors representing time constants of 3 to 28 days. Players performed a countermovement jump for estimation of a measure of neuromuscular recovery (ratio of flight time to contraction time, FT:CT), and provided a saliva sample for measurement of testosterone and cortisol concentrations 1 d prior to each of 34 matches. Match performance was assessed via ratings provided by five coaching and fitness staff on a 5-point Likert scale. Effects of training load on FT:CT, hormone concentrations, and match performance were modeled as quadratic predictors and expressed as changes in the outcome measure for a change in the predictor of one within-player standard deviation (1 SD) below and above the mean. Changes in each of five playing positions were assessed using standardization and magnitude-based inference. Results: The largest effects of training were generally observed in the 3- to 14-d windows. Center defenders showed a small reduction in coach rating when 14-d smoothed load increased from -1 SD to the mean (-0.31, ±0.15; mean, ±90% confidence limits), whereas strikers and wide midfielders displayed a small increase in coach rating when load increased 1 SD above the mean. The effects of training load on FT:CT were mostly unclear or trivial, but effects of training load on hormones included a large increase in cortisol (102, ±58 %) and a moderate increase in testosterone (24, ±18 %) in center defenders when 3-d smoothed training load increased 1 SD above the mean. A 1 SD increase in training load above the mean generally resulted in substantial reductions in testosterone:cortisol ratio. Conclusion: The effects of recent training on match performance and hormones in A-League football players highlight the importance of position-specific monitoring and training.